2022
DOI: 10.3390/healthcare10091603
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Active Mobility and Subjective Wellbeing during COVID-19 in MENA Countries

Abstract: Objective: To augment the international scientific approach to raising public mental health through active lifestyle among adults, we added the evidence of the association between physical activity and subjective wellbeing in the Middle East and North Africa region by emphasizing the mediator—COVID-19. This study aimed to identify the correlations between active mobility and subjective wellbeing during the COVID-19 pandemic in a sample from Tabriz, Iran, which has not yet been tackled in previous study. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 97 publications
(125 reference statements)
0
2
0
Order By: Relevance
“…Notably, the influence of open spaces on sport engagement has been an area of considerable interest among urban planners and researchers. Ranjbarnia et al (2022) found a strong correlation between the proximity of green spaces and the likelihood of individuals engaging in physical activities. Citizens with easy access to parks are more likely to participate in physical activities.…”
Section: Introductionmentioning
confidence: 92%
“…Notably, the influence of open spaces on sport engagement has been an area of considerable interest among urban planners and researchers. Ranjbarnia et al (2022) found a strong correlation between the proximity of green spaces and the likelihood of individuals engaging in physical activities. Citizens with easy access to parks are more likely to participate in physical activities.…”
Section: Introductionmentioning
confidence: 92%
“…When studying the factors influencing college students’ fitness app use, Yi considered fitness motivation, leisure, entertainment motivation, and structure rationality hardware requirements as antecedent variables of the perceived ease of use (PEOU) and perceived usefulness (PU) based on the technology acceptance model (TAM). Yi considered the perceived value variables as direct elements influencing university students’ mindset toward health app use [ 17 ]. The empirical findings showed that PEOU, PU, and perceived price positively affected college students’ attitudes toward using mobile fitness apps.…”
Section: Literature Reviewmentioning
confidence: 99%